Margaret MacCurtain (1929–2020): an appreciation. Issue 170 (November 2022) - O'Dowd, Mary
Abstract : 'Wisdom it was I loved and searched for her from my youth. I resolved to have her as my companion. I fell in love with her beauty ….' At the funeral mass for Margaret MacCurtain, her grandnephew, Michael, read the first reading from the Book of Wisdom, a moving and appropriate text with which to begin a celebration of Margaret's life. The words carried an added significance as Michael's reading emphasised that wisdom was represented in the biblical verse as female.